2003
DOI: 10.1128/iai.71.7.4175-4177.2003
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors and Clonal Relationships among Escherichia coli Strains Isolated from Broiler Chickens with Cellulitis

Abstract: In this study, we compared Escherichia coli isolates from chickens with avian cellulitis with those from feces of healthy chickens. Cellulitis-derived strains presented phenotypic and genotypic characteristics of greater virulence than did the fecal isolates. Phylogenetic analysis by repetitive extragenic palindromic-PCR showed that, in agreement with their virulence characteristics, the cellulitis isolates form two clonal groups distinct from the fecal isolates.Escherichia coli causes a variety of diseases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 10 publications
4
32
0
2
Order By: Relevance
“…A clonal diversity study with commensal avian E. coil strains and APEC strains performed by Silveira et al (2002b), using ERIC-PCR, demonstrated a relationship between the pathogenicity and the clonal origin of APEC strains. These observations were also made by Brito et al (2003) in APEC strains isolated from chickens with cellulitis. White et al (1993), using multilocus enzyme electrophoresis (MLEE), observed that APEC strains causing septicemia in turkeys belonged to a mixture of specialized pathogenic clones and non-pathogenic opportunist clones.…”
Section: Clonal Relationship and Pathogenic Clone Detectionmentioning
confidence: 82%
“…A clonal diversity study with commensal avian E. coil strains and APEC strains performed by Silveira et al (2002b), using ERIC-PCR, demonstrated a relationship between the pathogenicity and the clonal origin of APEC strains. These observations were also made by Brito et al (2003) in APEC strains isolated from chickens with cellulitis. White et al (1993), using multilocus enzyme electrophoresis (MLEE), observed that APEC strains causing septicemia in turkeys belonged to a mixture of specialized pathogenic clones and non-pathogenic opportunist clones.…”
Section: Clonal Relationship and Pathogenic Clone Detectionmentioning
confidence: 82%
“…Cellulitis is one of the most prevalent extraintestinal infections caused by APEC in broiler chickens, and is characterized by the presence of subcutaneous fibrinonecrotic plaques and inflammation of the overlying chicken skin, resulting in rejection of part or all of the carcasses at processing [2], [3], [4], [5]. In Brazil, cellulitis lesions are estimated to cause the loss of 0.14 to 1.4% of poultry meat production [6], leading to losses of at least 18 thousand tons of meat in 2011 [7].…”
Section: Introductionmentioning
confidence: 99%
“…As aves, cujos tratamentos sofreram desafio, foram inoculadas no 5º e 45º dia do período experimental, com cepas de E. coli, isoladas pela primeira vez por Brito et al (2003). Foi inoculada em cada ave, individualmente com agulha e seringa de insulina estéreis, pela via subcutânea, na região torácica esquerda, 0,1mL de E. coli na concentração de 10 8 UFC/mL.…”
Section: Methodsunclassified